2019
DOI: 10.1007/s00276-018-02176-6
|View full text |Cite
|
Sign up to set email alerts
|

Case report: absence of the right piriformis muscle in a woman

Abstract: We report a very rare case of a unilaterally absent piriformis muscle in a 60 year old woman. Accompanying variations comprised a common gluteal artery (instead of two distinct superior and inferior gluteal arteries), and an absent gemellus inferior muscle. The contralateral left side showed a normally developed piriformis muscle. In hominoids, the piriformis is constant, but is regularly missing in several other vertebrates. The piriformis muscle is an anatomical landmark for ultrasound investigations and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In the literature, there are several variations of the piriformis described -divided piriformis, cleavage of muscle bellies, merging with other muscles, or even absence. [4,5] The most important muscle variations, however, are those related to the structure of the proximal sciatic nerve. [6] Six basic types of piriformis-sciatic nerve varitions are described in the literature and their distribution among the human population are presented in details.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are several variations of the piriformis described -divided piriformis, cleavage of muscle bellies, merging with other muscles, or even absence. [4,5] The most important muscle variations, however, are those related to the structure of the proximal sciatic nerve. [6] Six basic types of piriformis-sciatic nerve varitions are described in the literature and their distribution among the human population are presented in details.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ikidag 8 presented a case with left flank pain but with contralateral piriformis agenesis. Brenner et al 7 reported in a cadaveric dissection case, piriformis agenesis, an ipsilateral common gluteal artery and an absent inferior gemellus muscle. In our case, the patient had progressively worsening low back pain radiating to both legs without neurological deficits on examination.…”
Section: Agenesis Of the Piriformis Musclementioning
confidence: 97%
“…Following an extensive literature review, only a handful of case reports on the absence or agenesis of the piriformis muscle are documented. 5,7,8 Only two cases have been reported in living human subjects. 5,8 Because of the rarity in incidence, not much is known about the presenting symptoms, clinical findings and sequelae of piriform agenesis.…”
Section: Agenesis Of the Piriformis Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Important neurovascular structures pass through infrapiriform foramen, including sciatic nerve [2]. In literature, case examples with variations of no or two piriformis have been reported [8][9][10][11].…”
Section: Topographic and Clinical Anatomy Of Piriformis Musclementioning
confidence: 99%